Design and synthesis of silicon-containing fatty acid amide derivatives as novel peroxisome proliferator-activated receptor (PPAR) agonists. Issue 16 (15th August 2015) - Kajita, Daisuke; Nakamura, Masaharu; Matsumoto, Yotaro; Ishikawa, Minoru; Hashimoto, Yuichi; Fujii, Shinya
Graphical abstract: Abstract: We recently reported that diphenylsilane structure can function as a cis -stilbene mimetic. Here, we investigate whether silyl functionality can also serve as a mimetic of aliphatic cis -olefin. We designed and synthesized various silyl derivatives of oleoylethanolamide (OEA:8 ), an endogenous cis -olefin-containing PPARα agonist, and evaluated their PPARα/δ/γ agonistic activity. We found that diethylsilyl derivative20 exhibited PPARα/δ agonistic activity, and we also obtained a PPARδ-selective agonist, 32 . Our results suggest that incorporation of silyl functionality is a useful option for structural development of biologically active compounds.